"Foucault and Critical Animal Studies: Genealogies of Agricultural Power". Issue 6 (6th June 2013) - Taylor, Chloë
Abstract Michel Foucault is well known as a theorist of power who provided forceful critiques of institutions of confinement such as the psychiatric asylum and the prison. Although the invention of factory farms and industrial slaughterhouses, like prisons and psychiatric hospitals, can be considered emblematic moments in a history of modernity, and although the modern farm is an institution of confinement comparable to the prison, Foucault never addressed these institutions, the politics of animal agriculture, or power relationships between humans and other animals more generally. The few times that Foucault discussed animality or human–animal relations, animals and animality remained metaphors for humans and human experiences. Despite Foucault's failure to analyze human–nonhuman animal relations, a significant body of Critical Animal Studies literature has mobilized Foucault's work over the last decade. In particular, a number of scholars have taken up Foucault's writings to consider how relations between humans and nonhuman animals in agriculture might be conceptualized as instances of sovereign power, biopower, disciplinary power, and pastoral power, as well as why we may not think that these are power relations at all. This essay provides an overview of Foucault's accounts of power and of the Foucauldian scholarship that applies these accounts to human–nonhuman animal relations in animal agriculture.